2017
DOI: 10.1139/apnm-2017-0217
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocalized postactivation performance enhancement (PAPE) effects in trained athletes: a pilot study

Abstract: Fifteen trained athletes were assessed for postactivation performance enhancement (PAPE) of squat jumps (SJs) and power push-ups (PPUs) following upper body activation, lower body activation, upper and lower body activation, and rest. SJ improved similarly across all 4 conditions. PPU could not be assessed. Since the test protocol of SJ and PPU involved upper and lower body activation and caused PAPE in SJ, future work is required to determine if a nonlocalized PAPE effect exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
112
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 18 publications
1
112
2
7
Order By: Relevance
“…These results were not as hypothesized and are in partial agreement with some previous literature [2,8,13,23]. The most likely explanation for the results found within the present study is that the warm-up and/or baseline measurements were enough to elicit a PAP response, as previously found by Cuenca-Fernández et al [7].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results were not as hypothesized and are in partial agreement with some previous literature [2,8,13,23]. The most likely explanation for the results found within the present study is that the warm-up and/or baseline measurements were enough to elicit a PAP response, as previously found by Cuenca-Fernández et al [7].…”
Section: Discussionsupporting
confidence: 90%
“…Dabbs et al [8] reported increases in vertical jump performance, but at individual rest intervals. Also, Cuenca-Fernández et al [7] found that the warm-up protocol and baseline measurement were enough to elicit potentiation. These equivocal results related to PAP as a performance enhancing strategy could be due to a wide range of study designs utilized such as outcome measures, type of muscular contraction, exercise selection, intensity, subject characteristics (sex, strength, age, etc.…”
Section: Introductionmentioning
confidence: 99%
“…suggested that "postactivation performance enhancement" be used when referring to the enhancement observed following voluntary contractions (Blazevich & Babault, 2019;Cuenca-Fernández et al, 2017). Therefore, this terminology will be used throughout when discussing voluntary contractions.…”
mentioning
confidence: 99%
“…The inclusion of conditioning exercises in a warm-up, i.e., high-intensity exercises, is widely thought to potentiate performance [6,7]. "Post-activation performance enhancement" (PAPE) is a new term introduced by Cuenca-Fernández et al [8] and describes such effects. In contrast to the classic post-activation potentiation, i.e., an increase in twitch force and power after electrically or voluntarily induced intense contraction [9,10], PAPE has a longer and weaker effect on performance, and is more likely attributed to different mechanisms [11]; the former is attributed to the phosphorylation of the myosin regulatory light-chain and the latter to changes in muscle temperature, muscle/cellular water content and/or muscle activation [11].…”
Section: Introductionmentioning
confidence: 99%